Major congenital defects. Relevant risk factors. Cienfuegos. 2000-2005. - Vivian Vázquez Martínez; Cristóbal Torres González; Gabriel González Jiménez; Yobadis Hernández del Sol; Ana López Rodríguez del Rey; Gladis Barberis Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Major congenital defects have an impact on perinatal mortality and morbidity with economic and social consequences. Objective: To determine the relevant risk factors linked to the occurrence of congenital defects in Cienfuegos between 2000 and 2005. Methods: A case-control study was carried out. Women with fetus or newborns with major congenital defects formed the case group (255) while the control group consisted of a similar number of healthy children selected each year by a randomized simple sample. The variables gathered by the Cuban Congenital Defects Records were studied. Chi-Square method was used with 95% of accuracy and a reliance rate of 95%; logistic regression was used with the Wald test. Results: There was a predominance of Central Nervous System defects (28, 6%). The most relevant risk factors were a history of congenital defects, smoking habits, and acute infection during the first three months, as well as belong to the third birth on. Conclusion: The most clinical relevant risks factors were the congenital defect history and the acute infection during the firs three months.